Nation Building: The Role of Central Spending in Education - Francesco Cinnirella; Ruth Maria Schueler (Center for Economic Studies and ifo Institute (CESifo), 2016)
It is generally argued that, in the context of Imperial Germany, public primary education was used to form “loyal citizens” and to build a nation. In this paper we analyze to what extent central spending on primary education affected participation at general elections and votes for pro-nationalist parties. We combine census data on the sources of school funding with federal elec-tion data at the level of 199 constituencies in five-year intervals from 1886 to 1911. Panel esti-mates of models with constituency and time-fixed effects show that an increase in the share of central spending is positively related to the vote share of pro-nationalist parties and voter turnout. Results from models with lagged central spending by category of expenditure are consistent with the role of indoctrination of public primary education.
Keywords: N33; N43; H72; I28; 330; nation building; primary education; indoctrination; Prussian economic history